Active Learning Strategies in Improving Middle School Students' Mathematical Abilities - Wardini, Sevia Umi; Trisnantari, Hikmah Eva (Yayasan Indonesia Emerging Literacy Education, 2024)
Ability communication mathematics have role Which very important in learning mathematics. In mathematics ability Mathematical communication acts as a tool that students use in learning put forward idea Which they have For build knowledge the math. The low ability communication mathematical student influenced by many factors both internal and external. One of the research focuses This looks at external factors namely the learning strategy factor. To improve students' mathematical communication skills, then from teachers need to apply appropriate learning strategies. One strategy that can give chance to student role active in communicating knowledge is an Active Learning learning strategy type tutors peer.This research aims to determine the increase in students' mathematical communication skills after implementing the peer tutoring Active Learning strategy.Approach Which done in study This use approach quantitative. Approach quantitative is an approach based on interpretation of data in the form of numbers. Design study Which will used in study This is study quasi experimenter. On study This, type design Which used researcher that is design control group pretest-posttest design. The data collection technique used in this research is a test. The instruments used in this research are learning tools and test sheets.Based on the results of the research carried out, the conclusion is that the mathematical communication skills of students who apply the Active Learning learning strategy with the peer tutor type improve compared to expository learning.